A simple tool to predict exercise capacity of obese patients with ischaemic heart disease. Issue 7 (9th December 2005) - Gondoni, L A; Liuzzi, A; Titon, A M; Taronna, O; Nibbio, F; Ferrari, P; Leonetti, G
Abstract : Objective: To define an equation that predicts exercise capacity taking into account body mass index (BMI). Design: Retrospective analysis and validation study of a multidisciplinary programme aimed at weight loss and physical rehabilitation. Setting: Tertiary referral hospital. Patients and methods: 372 consecutive obese participants (249 men) with stable ischaemic heart disease, aged mean 60.1 (SD 8.7) years, underwent a treadmill exercise test. BMI was 37.8 (4.5) kg/m 2 . In the validation study the model was tested in 87 patients with similar characteristics. Results: Mean exercise intensity was 6.6 (SD 2.4) metabolic equivalents (METs). Multivariate linear regression analysis defined two simple models that considered exercise intensity as the dependent variable and a set of independent variables such as anthropometric measures, age and sex in the first one, plus associated clinical conditions and drug treatment in the second one. The correlation coefficients of the two models were R = 0.630 and R = 0.677, respectively. Age, BMI and sex were the strongest predictors of exercise capacity. The first derived equation efficiently predicted exercise capacity: in the validation study predicted exercise intensity was 6.3 (1.6) METs and attained exercise intensity was 6.3 (2.4) METs (p = 0.903) with a highly significant correlation ( R = 0.534, p < 0.001). Conclusion: BMI is an important determinant of exercise capacity of obese people with ischaemic heart disease. The use of a simple equation may help in predicting exercise capacity, in individualising exercise protocol and in setting up rehabilitation programs for obese patients.